5-HT7 receptor activation promotes an increase in TrkB receptor expression and phosphorylation - Samarajeewa, Anshula; Goldemann, Lolita; Vasefi, Maryam S.; Ahmed, Nawaz; Gondora, Nyasha; Khanderia, Chandni; Mielke, John G.; Beazely, Michael A. (Frontiers in Behavioral Neuroscience, 2014)
The serotonin (5-HT) type 7 receptor is expressed throughout the CNS including cortical neurons. We have previously demonstrated that the application of 5-HT7 receptor agonists to primary hippocampal neurons and SH-SY5Y cells increases platelet-derived growth factor (PDGF) receptor expression and promotes neuroprotection against N-methyl-D-aspartate-(NMDA)-induced toxicity. The tropomyosin-related kinase B (TrkB) receptor is one of the receptors for brain-derived neurotrophic factor (BDNF) and is associated with neurodevelopmental and neuroprotective effects. Application of LP 12 to primary cerebral cortical cultures, SH-SY5Y cells, as well as the retinal ganglion cell line, RGC-5, increased both the expression of full length TrkB as well as its basal phosphorylation state at tyrosine 816. The increase in TrkB expression and phosphorylation was observed as early as 30 min after 5-HT7 receptor activation. In addition to full-length TrkB, kinase domain-deficient forms may be expressed and act as dominant-negative proteins towards the full length receptor. We have identified distinct patterns of TrkB isoform expression across our cell lines and cortical cultures. Although TrkB receptor expression is regulated by cyclic AMP and Gαs-coupled GPCRs in several systems, we demonstrate that, depending on the model system, pathways downstream of both Gαs and Gα12 are involved in the regulation of TrkB expression by 5-HT7 receptors. Given the number of psychiatric and degenerative diseases associated with TrkB/BDNF deficiency and the current interest in developing 5-HT7 receptor ligands as pharmaceuticals, identifying signaling relationships between these two receptors will aid in our understanding of the potential therapeutic effects of 5-HT7 receptor ligands.